Can the phenotype of inherited fibrinogen disorders be predicted?. (13th June 2016) - Casini, A.; de Moerloose, P.
Abstract : Congenital fibrinogen disorders are rare diseases affecting either the quantity (afibrinogenaemia and hypofibrinogenaemia) or the quality (dysfibrinogenaemia) or both (hypodysfibrinogenaemia) of fibrinogen. In addition to bleeding, unexpected thrombosis, spontaneous spleen ruptures, painful bone cysts and intrahepatic inclusions can complicate the clinical course of patients with quantitative fibrinogen disorders. Clinical manifestations of dysfibrinogenaemia include absence of symptoms, major bleeding or thrombosis as well as systemic amyloidosis. Although the diagnosis of any type of congenital fibrinogen disorders is usually not too difficult with the help of conventional laboratory tests completed by genetic studies, the correlation between all available tests and the clinical manifestations is more problematic in many cases. Improving accuracy of diagnosis, performing genotype, analysing function of fibrinogen variants and carefully investigating the personal and familial histories may lead to a better assessment of patients' phenotype and therefore help in identifying patients at increased risk of adverse clinical outcomes. This review provides an update of various tests (conventional and global assays, molecular testing, fibrin clot analysis) and clinical features, which may help to better predict the phenotype of the different types of congenital fibrinogen disorders.